Explaining Symptoms in Systemic Therapy. Does Triadic Thinking Come Into Play? - Ugazio, Valeria; Pennacchio, Roberto; Fellin, Lisa; Guarnieri, Stella; Anselmi, Pasquale (Frontiers in Psychology, 2020)
The main aim of this study is to explore the breadth of the inference field and the type of etiopathogenetic contents of symptom explanations provided by the client and therapist in the first two psychotherapy sessions conducted using a systemic approach. Does the therapist use triadic explanations of psychopathology as suggested by her approach? And do clients resort almost exclusively to monadic and dyadic explanations as did the university students in our previous study? What kind of explanations do they propose? The coding system “1 to 3: from the monad to the triad” was applied to the transcripts of 25 individual systemic therapies conducted by the same therapist. This manual allows to code the inference field of symptom explanations according to three categories: monadic, dyadic and triadic. These three broad categories are also used to analyse the etiopathogenetic content of each explanation: traumatic, intrapersonal, and interpersonal. Our findings showed that clients and their therapist actually used different inference fields: clients resorted almost exclusively to monadic and dyadic explanations, whereas their therapist included the triadic explanatory level. Moreover, the therapist provided more interpersonal explanations than her clients. Hence, the dissonance between client and therapist about the inference fields¬–a crucial premise of one of the most accepted ideas of therapeutic change according to systemic therapies–is proved, at least among our participants. Thanks to this dissonance, clients and therapists can create a new story, potentially able to change clients’ feelings, without disconfirming their emotions.